Influence of pharmacology drugs on the forms of blood elements - Maskaeva, V. S.; Filkevych, O. O.; Sokolovska, I. A.; Соколовська, Ірина Анатоліївна (Запорізький державний медичний університет, 2022)
The purpose of this presentation is to study the effect of drugs on erythrocytes.
Keywords: тези доповідей